Digital Signature Legality And Evidence In Trials - Devi Cintiya Ramadhanti; Pujiyono Pujiyono (LPPM Universitas PGRI Sumatera Barat, 2022)
Currently, the dynamics of Indonesian society are at the growing industrial and information society stage in which one example is the presence of the digital signature. Indonesia has not yet familiar with legislation concerning digital signatures. This is a fundamental issue in proving in court as the law does not yet recognize the existence of electronic-based data as legal evidence. This article tries to explain, inventory, and evaluate the validity and legality of digital signatures and the process of proof in court. This normative study used a conceptual approach starting from ideas and thoughts in legal science. The emergence of digital signatures through a legal basis, namely the Electronic Information and Transaction Law (ITE Law) strengthens the recognition of the validity of signatures on a contract or electronic transaction. The recognition of the validity of documents including digital signatures as evidence after the issuance of the ITE Law proves the expansion of civil procedural law in this country. Digital signatures in electronic transactions are considered valid and have the power of a deed issued by an authorized official. In order to make a digital signature in an electronic document have the power of proof in court, it has to be registered with the Certification Authority (CA).